Combinatorial expression of different β-carotene hydroxylases and ketolases in Escherichia coli for increased astaxanthin production. (1st November 2019) - Wu, Yuanqing; Yan, Panpan; Liu, Xuewei; Wang, Zhiwen; Tang, Ya-Jie; Chen, Tao; Zhao, Xueming
Abstract: In natural produced bacteria, β-carotene hydroxylase (CrtZ) and β-carotene ketolase (CrtW) convert β-carotene into astaxanthin. To increase astaxanthin production in heterologous strain, simple and effective strategies based on the co-expression of CrtZ and CrtW were applied in E. coli . First, nine artificial operons containing crtZ and crtW genes from different sources were constructed and, respectively, introduced into E. coli ZF237T, a β-carotene producing host. Among the nine resulting strains, five accumulated detectable amounts of astaxanthin ranging from 0.49 to 8.07 mg/L. Subsequently, the protein fusion CrtZ to CrtW using optimized peptide linkers further increased the astaxanthin production. Strains expressing fusion proteins with CrtZ rather than CrtW attached to the N-terminus accumulated much more astaxanthin. The astaxanthin production of the best strain ZF237T/CrtZAs -(GS)1 -WBs was 127.6% and 40.2% higher than that of strains ZF237T/ crtZ   As   W   Bs and ZF237T/ crtZ   Bs   W   Ps, respectively. The strategies depicted here also will be useful for the heterologous production of other natural products.